THE PLACE OF TRANSILVANIA WITHIN THE POLITICAL AND ETHNIC FRAMEWORK OF THE ROMANIAN STATE - Ioan CHIȘ (Challenges of the Knowledge Society)
The First World War bought unimaginable suffering to the Romanian people, tragic consequences for thousands of families who saw their sons lives squandered on the fields of defense of the territory as well as the riches and wealth of the country destroyed and stolen for the benefit of looters who considered that the exploatation of the Romanian territories was a right of the winner. The payment for the sufferings has never been done for the families of the Romanians, but the history of Transylvania and the Romanian lands has the mercy to place all Romanians in their place next to the ethnic homeland, as it was written in the eternal and fascinating fate of Dacia Felix. Now, 100 years after the union, the sun of the Romanians, from Bucharest, pale and hidden among the clouds of neighboring intterests, like then, tries to shine through the eyes and souls of the three brothers: the Vallachian, the Moldavian and the Transilvanian.